The Role of Youth in the Marketing of Ponot Water Tourism for Regional Development in Asahan District - Anazmi, Feby; Revida, Erika; Purwoko, Agus (Journal of Environmental and Development Studies, 2021)
The purpose of this study is to look at the role of youth in Asahan Regency in marketing Ponot Waterfall Tourism. This research focuses on the role that has been carried out by young people in Asahan Regency in marketing Ponot Waterfall Tourism to become a leading tourist in Asahan Regency.The development of the Ponot Waterfall Tourism Area is inseparable from the role of Asahan Regency youth who consistently and innovatively market the Ponot Waterfall Tourism area to become one of the leading tourist destinations in Asahan Regency. The method used in this research is descriptive method with a qualitative approach. This study took primary data through informants and secondary data from relevant agencies, namely the Asahan Regency Sports and Tourism Youth Service, Asahan KNPI, the Regency Statistics Agency.The results of the study indicate that the role of Asahan Regency youth in marketing Ponot Waterfall tourism for regional development is that youth play a role as social control, moral strength and agents of change.